SYSITEMATIC LITERATURE REVIEW: STANDAR PENGELOLAAN PENDIDIKAN DASAR - Septi Zulefni, Marshella; Aldania Efendi, Raesa; Fitriani, Yuni; Ananda, Rizki (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
This research aims to conduct a systematic literature review on the standards of basic education management. The method used in this study is a systematic literature review, where various relevant literature sources are collected and comprehensively analyzed. This research identifies several standards of basic education management regulated by the Minister of National Education of the Republic of Indonesia Regulation No. 19 of 2007. These standards encompass aspects such as program planning, implementation of work plans, supervision, evaluation, school/madrasah leadership, and management information systems. Through literature analysis, it is found that effective and standards-compliant education management plays a crucial role in creating efficient and effective education. This research also highlights the importance of the involvement of local governments in education management, especially at the basic education level. Keywords: basic education, management, standard